A Feasibility Study on Botak Compresour - Borja, Ben Monta Jr.; Urgino, Suzanne Margaret D. (Diliman, Quezon City College of Engineering, 1995)
MARKET ANALYSIS. There is an existing unsatisfied demand for basketball shorts with built-in compression shorts. Out of 276 respondents to a survey conducted, 51.61% preferred to wear built-in compression shorts over separate sports gear, and 72.84% of the respondents were willing to buy the product. Target market is 15.5% of the total Philippine population. This comprises (1) male (2) teenagers and young professionals, (3) within the ages 15 to 29 years, (4) falling under the social classes A, B, C and D, and (5) located within the following six cities: Manila, Mandaluyong, Makati, Marikina, San Juan and Quezon City. Demand projections linearly increases from 6,062 units/year during its introduction stage to 24,696 units in its maturity stage (four years from start of production). This demand largely depends on the consumers' awareness of the existence of the product, therefore, it is recommended that the product be manufactured by Cejogua Sports Corporation (CSC), the company manufacturing Botak sports swear. This recommendation is based on the following: (1) CSC has a 30% market share of sports wear industry, (2) the brand name Botak provides the product with a better name recall for consumers, (3) CSC has already established a reputation for providing quality sports wear, (4) the company has the experience and capacity to produce the product. The recommended brand name for the product venture is Botak Compresour. TECHNICAL ANALYSIS. Botak Compresours can be manufactured at a quantity equal to the projected demand plus 5% allowance for deviations of actual demand from projections. The demand can be met if the plant capacity is adjusted proportionately. Annual increase in capacity is as follows: for 1996, the 8,000 units, 1999 capacity increases by 500 and remains at the level of 9,300 units per month capacity from then on. At the current CSC plant production rate, the first year demand of 6,062 units can be satisfied given that the product is manufactured during months where the plant load is less than the maximum plant capacity. Months falling under this category excludes March, April and July. FINANCIAL ANALYSIS. The product can operate profitably given that the sales of Botak Compresour is equal to the projected demand. First year gross sales is computed as P3,317,601.27 increasing to 29,116,400.72 in ten years duration. Start-up cost of P1,675,083.01 can be funded through a loan of P1.7 million payable in ten years at 12% per annum interest . The Debt Coverage Ration is always greater than 100%, this means that the debt earns sufficient profits for debt coverage. Net income linearly increases annually. Net income for the first four years is P316,869.12, P875,372.62, P1,216,016.95 and P3,098,303.36 respectively. In the event of adversities, the project is evaluated to be relatively stable. Current ratio is 9.97 in 1996 and liquidity of inventory is 6.42 which increases to 7.19 in 2005. Capital is utilized optimally based on the asset turnover of 89%. Average rate of return of the project is 10.65. SOCIO-PROFITABILITY. Social and economic contributions of the product are in the form of income and sales taxes paid to the government and support of related industries from annual raw material purchases. Annual taxes paid for 1996 is P331,760.13. Government share in gross sales is 10%, while share of related industries (raw materials supplier) to operating profit is 114%.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 153 : Project Development and Management
Keywords: Cejogua Sports Corporation (CSC); Basketball uniforms; Participatory monitoring and evaluation (Project management)